2020 IEEE 10th Symposium on Large Data Analysis and Visualization (LDAV) 2020
DOI: 10.1109/ldav51489.2020.00008
|View full text |Cite
|
Sign up to set email alerts
|

Data Parallel Hypersweeps for in Situ Topological Analysis

Abstract: The contour tree is a tool for understanding the topological structure of a scalar field. Recent work has built efficient contour tree algorithms for shared memory parallel computation, driven by the need to analyze large data sets in situ while the simulation is running. Unfortunately, methods for using the contour tree for practical data analysis are still primarily serial, including single isocontour extraction, branch decomposition and simplification. We report data parallel methods for these tasks using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In each iteration, monotone chains of superarcs transfer as hyperarcs to the contour tree -i.e. a specialised form of branch decomposition [24] that is related to rake-reduce parallel tree algorithms [16]. In this way, a hyperstructure is built up that allows logarithmic search in the contour tree for efficient parallel processing.…”
Section: Parallel Peak Pruningmentioning
confidence: 99%
See 2 more Smart Citations
“…In each iteration, monotone chains of superarcs transfer as hyperarcs to the contour tree -i.e. a specialised form of branch decomposition [24] that is related to rake-reduce parallel tree algorithms [16]. In this way, a hyperstructure is built up that allows logarithmic search in the contour tree for efficient parallel processing.…”
Section: Parallel Peak Pruningmentioning
confidence: 99%
“…In subsequent work [16], we then showed that the hyperstructure was also related to the Euler Tour [4], which allows computations over trees to be collapsed into prefix sum operations. By exploiting this, we demonstrated efficient shared-memory parallel computation of geometric measures, simplification, branch decomposition and isocontour extraction.…”
Section: Parallel Peak Pruningmentioning
confidence: 99%
See 1 more Smart Citation